Practical design of timber structures to Eurocode 5 - Larsen, Hans Jrgen (Thomas Telford, 2009)
Written by leading experts in the field, including one of the authors of Eurocode 5, this practical book provides a comprehensive guide to the design of timber structures according to the latest European and UK standards.